Infertility services integrated within the maternal health department of a public hospital in a low-income country, Rwanda - Selwyn P. Oskowitz, M.D; Angélique K. Rwiyereka, M.D., Ph.D; Théogène Rurangwa, M.D; Donald S. Shepard, Ph.D; Emile Rwamasirabo, M.D; Keith B. Isaacson, M.D; Sheryl van der Poel, Ph.D; Catherine Racowsky, Ph.D (Elsevier, 2023)
Objective: To describe the initiation, integration, and costs of reduced-cost infertility services within the maternal health department of a public hospital in a low-income country. Design: Retrospective review of the clinical and laboratory components of patients undergoing in vitro fertilization (IVF) treatment in Rwanda from 2018 to 2020. Setting: Academic tertiary referral hospital in Rwanda. Patients: Patients seeking infertility services beyond the primary gynecological options. Interventions: The national government furnished facilities and personnel, and the Rwanda Infertility Initiative, an international nongovernmental organization, provided training, equipment, and materials. The incidence of retrieval, fertilization, embryo cleavage, transfer, and conception (observed until ultrasound verification of intrauterine pregnancy with fetal heartbeat) were analyzed. Cost calculations used the government-issued tariff specifying insurers' payments and patients' copayments with projected delivery rates using early literature. Main Outcome Measures: Assessment of functional clinical and laboratory infertility services and costs. Results: A total of 207 IVF cycles were initiated, 60 of which led to transfer of ≥1 high-grade embryo and 5 to ongoing pregnancies. The projected average cost per cycle was 1,521 USD. Using optimistic and conservative assumptions, the estimated costs per delivery for women <35 years were 4,540 and 5,156 USD, respectively. Conclusions: Reduced-cost infertility services were initiated and integrated within a maternal health department of a public hospital in a low-income country. This integration required commitment, collaboration, leadership, and a universal health financing system. Low-income countries, such as Rwanda, might consider infertility treatment and IVF for younger patients as part of an equitable and affordable health care benefit.